The lncRNA-AK046375 Upregulates Metallothionein-2 by Sequestering miR-491-5p to Relieve the Brain Oxidative Stress Burden after Traumatic Brain Injury. (16th February 2022) - Tang, Wei; Chai, Weina; Du, Donglin; Xia, Yongzhi; Wu, Yifan; Jiang, Li; Cheng, Chongjie; Guo, Zongduo; Sun, Xiaochuan; Huang, Zhijian; Zhong, Jianjun
Abstract : We previously discovered that traumatic brain injury (TBI) induces significant perturbations in long noncoding RNA (lncRNA) levels in the mouse cerebral cortex, and lncRNA-AK046375 is one of the most significantly changed lncRNAs after TBI. lncRNA-AK046375 overexpression and knockdown models were successfully constructed both in vitro and in vivo . In cultured primary cortical neurons and astrocytes, lncRNA-AK046375 sequestered miR-491-5p, thereby enhancing the expression of metallothionein-2 (MT2), which ameliorated oxidative-induced cell injury. In addition, upregulated lncRNA-AK046375 promoted the recovery of motor, learning, and memory functions after TBI in C57BL/6 mice, and the underlying mechanism may be related to ameliorated apoptosis, inhibited oxidative stress, reduced brain edema, and relieved loss of tight junction proteins at the blood-brain barrier in the mouse brain. Therefore, we conclude that lncRNA-AK046375 enhances MT2 expression by sequestering miR-491-5p, ultimately strengthening antioxidant activity, which ameliorates neurological deficits post-TBI.